2013
DOI: 10.1208/s12248-013-9456-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery and Regulatory Considerations for Improving In Silico and In Vitro Predictions that Use Caco-2 as a Surrogate for Human Intestinal Permeability Measurements

Abstract: ABSTRACT. There is a growing need for highly accurate in silico and in vitro predictive models to facilitate drug discovery and development. Results from in vitro permeation studies across the Caco-2 cell monolayer are commonly used for drug permeability screening in industry and are also accepted as a surrogate for human intestinal permeability measurements by the US FDA to support new drug applications. Countless studies carried out in this cell line with published permeability measurements have enabled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 136 publications
7
123
0
2
Order By: Relevance
“…Finally, low permeability compounds were highly represented as substrates of hepatic basolateral uptake transporters (32). Importantly, their data indicate that in vitro permeability rate can be used as a surrogate for extent of metabolism for new molecular entities (NMEs) when clinical data is unavailable, as has been proposed by our laboratory (31,33,34). Specifically, compounds with permeability rates equal to or exceeding a standard, e.g., metoprolol, are likely extensively metabolized in vivo in humans, while those with permeability rates lower than the standard are likely eliminated primarily as unchanged drug in either the bile or the urine.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, low permeability compounds were highly represented as substrates of hepatic basolateral uptake transporters (32). Importantly, their data indicate that in vitro permeability rate can be used as a surrogate for extent of metabolism for new molecular entities (NMEs) when clinical data is unavailable, as has been proposed by our laboratory (31,33,34). Specifically, compounds with permeability rates equal to or exceeding a standard, e.g., metoprolol, are likely extensively metabolized in vivo in humans, while those with permeability rates lower than the standard are likely eliminated primarily as unchanged drug in either the bile or the urine.…”
Section: Introductionmentioning
confidence: 85%
“…Prior to any studies in animals or humans for an NME, in vitro permeability data, as demonstrated by Varma et al (32) and initially proposed by our laboratory (4,33,34), can identify which drugs are primarily eliminated by metabolic or non-metabolic (biliary, renal) routes. Highly permeable drugs are likely extensively metabolized in vivo.…”
Section: Application To New Molecular Entitiesmentioning
confidence: 99%
“…However, in spite of this achievement, as well as the various developments detailed above, it also needs to be noted that we are a long way from precise prediction of human bioavailability. Several examples are available of instances where in silico and in vitro predictive models based on Caco-2 permeability measurements do not correlate with human intestinal permeability (Larregieu and Benet, 2013).…”
Section: Synthetic Membrane Systemsmentioning
confidence: 99%
“…Though Caco-2 cells are proficient in the main transporters, including P-glycoprotein (PgP), multidrug resistance protein 2 (MRP2), and breast cancer resistance proteins (BCRP), expression levels of these transporters are generally quite variable (Larregieu and Benet, 2013;Harwood et al, 2013Harwood et al, , 2016. In addition, the under-expression of transporters such as peptide transporter 1 (PEPT1), organic cation transporters (OCTs), and organic anion transporters (OATs), makes the model less suitable for compounds that use these transporters (Larregieu and Benet, 2013).…”
Section: In Vitro Methods For Assessing Kinetics Predictive Value Fomentioning
confidence: 99%
“…Though Caco-2 cells are proficient in the main transporters, including P-glycoprotein (PgP), multidrug resistance protein 2 (MRP2), and breast cancer resistance proteins (BCRP), expression levels of these transporters are generally quite variable (Larregieu and Benet, 2013;Harwood et al, 2013Harwood et al, , 2016. In addition, the under-expression of transporters such as peptide transporter 1 (PEPT1), organic cation transporters (OCTs), and organic anion transporters (OATs), makes the model less suitable for compounds that use these transporters (Larregieu and Benet, 2013). Under-expression of metabolic enzymes (e.g., CYP3A4) and different sulfotransferase and uridine diphospho-glucuronosyltransferase (UGT) enzymes, as compared to the human small intestine, also makes Caco-2 cells a poor model for studying intestinal metabolism (Gregory et al, 2004;Meinl et al, 2008;Peters et al, 2016;Schmiedlin-Ren et al, 1997).…”
Section: In Vitro Methods For Assessing Kinetics Predictive Value Fomentioning
confidence: 99%